2009
DOI: 10.3390/ma2041955
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube-Reinforced Thermotropic Liquid Crystal Polymer Nanocomposites

Abstract: This paper focuses on the fabrication via simple melt blending of thermotropic liquid crystal polyester (TLCP) nanocomposites reinforced with a very small quantity of modified carbon nanotube (CNT) and the unique effects of the modified CNT on the physical properties of the nanocomposites. The thermal, mechanical, and rheological properties of modified CNT-reinforced TLCP nanocomposites are highly dependent on the uniform dispersion of CNT and the interactions between the CNT and TLCP, which can be enhanced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 87 publications
0
32
0
Order By: Relevance
“…It was observed that η * decreased with increasing ω for neat TPER and UFC-filled composites, indicating a non-Newtonian behavior and pseudoplastic characteristics over the entire ω range studied (Wang et al 2008;Kim 2009;Barick and Tripathy 2011). This behavior can be explained as being due to the random orientation of the rigid molecular chains upon the application of shear force (Kim 2009). The UFC-filled composites exhibited higher η * than the neat TPER, especially at low frequencies.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…It was observed that η * decreased with increasing ω for neat TPER and UFC-filled composites, indicating a non-Newtonian behavior and pseudoplastic characteristics over the entire ω range studied (Wang et al 2008;Kim 2009;Barick and Tripathy 2011). This behavior can be explained as being due to the random orientation of the rigid molecular chains upon the application of shear force (Kim 2009). The UFC-filled composites exhibited higher η * than the neat TPER, especially at low frequencies.…”
Section: Resultsmentioning
confidence: 95%
“…The slopes of G' and G" decreased minimally with increasing UFC content in the TPER matrix ( Fig. 3a and b), and the decrease can be explained by the fact that UFC-UFC or UFC-TPER interactions can induce interconnected or network-like structures, leading to the pseudosolid-like behavior (Wang et al 2008;Kim 2009). Pseudo solid-like behavior was also reported for other cellulose-filled polymer systems (Shumigin et al 2011;Kiziltas et al 2014b;Kiziltas et al 2016a;Kiziltas et al 2016b).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Because the crystalline order between LCP polymer chains is maintained even at elevated temperatures, it is of great interest to determine how GO layers will disperse in LCP, and how the mechanical properties and electrical conductivity of the resulting materials will be modified. To the best of our knowledge, only limited studies are available on the effect of carbonaceous nanofillers on the physical and mechanical properties of LCPs [39][40][41][42]. Noteworthy, multifunctional materials such as LCP nanocomposites offer a great potential to enhance not only the mechanical and thermal properties with respect to the unmodified polymer, but also functional properties including high electrical and thermal conductivity, providing the opportunity to be used in different fields such as automotive, electronic packaging, aerospace, energy storage, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [80] used the Halpin-Tsai model to compare their experimental result to the theoretical ones. The L MWCNT /D MWCNT (aspect ratio) was taken as 1,000.…”
Section: Mechanical Properties Of Mwcnt/tlcp Nanocompositesmentioning
confidence: 99%